An Alternative Approach to Analyze Ipsative Data. Revisiting Experiential Learning Theory - Batista-Foguet, Joan M.; Ferrer-Rosell, Berta; Serlavós, Ricard; Coenders, Germà; Boyatzis, Richard E. (Frontiers in Psychology, 2015)
The ritualistic use of statistical models regardless of the type of data actually available is a common practice across disciplines. Statistical models involve a series of assumptions whose existence is often neglected altogether, thus making the mentioned common practice even more pervasive. This paper illustrates the consequences of this ritualistic practice within Kolb’s Experiential Learning Theory (ELT) operationalized through its Learning Style Inventory (KLSI). We show how using a well-known methodology in other disciplines -compositional data analysis (CODA)- KLSI data can be properly analyzed. In addition, a third dimension of the KLSI is unveiled providing room for future research. This third dimension describes an individual’s relative preference for learning by prehension rather than by transformation. Using a sample of European MBA students, we relate this dimension with another self-assessment instrument, the Philosophical Orientation Questionnaire (POQ), and with an observer-assessed instrument, the Emotional and Social Inventory (ESCI-U). Both show plausible statistical relationships. An intellectual operating philosophy is linked to a preference for prehension, whereas a pragmatic operating philosophy is linked to transformation. Self-management and social awareness competencies are linked to a learning preference for transforming knowledge, whereas relationship management and cognitive competencies are more related to approaching learning by prehension.